MODEL MANAJEMEN INOVATIF PROGRAM BBQ DALAM MEMBANGUN BUDAYA MADRASAH RAMAH ANAK BERBASIS NILAI-NILAI ISLAM DI MIN 3 JOMBANG - Isnainiyah, Lilik; Asna, Megawati Mahalil (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to describe the innovative management model of the BBQ Program (Line Up, Pray, and Quiz) in developing a child-friendly Islamic-based school culture at MIN 3 Jombang. The program was initiated to enhance students’ discipline, responsibility, and learning motivation through enjoyable habituation activities. The study used a qualitative descriptive approach with observation, interview, and questionnaire techniques involving teachers and students. The results indicate that the implementation of the BBQ Program effectively improved discipline, responsibility, queuing habits, self-confidence, and learning motivation. The BBQ Program is a managerial innovation that strengthens students’ religious values, nationalism, and independence. This finding highlights that innovative management based on Islamic values can successfully foster a child-friendly, religious, and character- oriented madrasah culture